A method for detecting surface defects of aluminum alloy plates
Through the detection method of electrolytic use of degreasing and acid polishing liquid, the problem of difficult to identify microcracks on the surface of aluminum alloy sheets in the prior art is solved, and efficient and low-cost detection is achieved, which is suitable for production sites.
Patent Information
- Application Number
- CN202210693337.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-17
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-06-17
AI Technical Summary
The prior art is difficult to effectively identify microcracks with a surface depth of less than 50μm in aluminum alloy sheets, and common detection methods require expensive high-precision instruments, which are complex in operation and are not suitable for production sites.
The detection method of electrolytic use of degreasing and acid polishing liquid is adopted to remove grease by degreasing treatment, and the electrolytic polishing method expands the depth of microcracks, improves the storage capacity of penetrants, and enhances the recognition ability of microcracks.
It realizes efficient identification of microcracks on the surface of aluminum alloy sheets, reduces detection costs, simplifies operating procedures, and is suitable for production sites.
Smart Images

Figure HDA0003701231820000011
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal material detection, and in particular to a method for detecting surface defects of an aluminum alloy plate, and in particular to a method for quickly detecting surface micro-defects of an aluminum alloy plate that is easy to identify. Background Art
[0002] As we all know, aluminum alloys have lower density, higher specific strength, better machinability and corrosion resistance than traditional steel materials. Currently, using aluminum alloys to replace steel materials in non-load-bearing parts is one of the main ways to achieve lightweight automotive structures.
[0003] However, compared with galvanized high-strength steel, the surface condition of aluminum alloy sheets is more complicated. The second phase particles in the aluminum alloy give the sheet unique mechanical properties, but also cause certain problems. During the rolling process, the deformation of the second phase particles and the sheet is often inconsistent, which leads to some cracks and other defects on the aluminum alloy sheet. When the gaps and height differences of these defective parts are large, it is difficult to cover these defective parts during the automobile pre-treatment process, and some defects in the pre-treatment process will occur.
[0004] At present, there are many methods for identifying surface defects of metal devices. For micro-crack defects on the surface of the plate, the more common detection method is the penetrant flaw detection method. However, the presence of impurities such as oxide film and grease on the surface of automotive plates will greatly hinder the penetration of colorants into the cracks. When the depth of the crack is less than 50μm, the crack has a poor storage capacity for colorants, resulting in unclear color development of the subsequent defective parts, making the final color development effect very poor. And most of these methods require the use of technical means such as ultrasound, X-rays and infrared rays. These high-precision instruments are not only expensive, but also require relevant operators to have corresponding knowledge and operating skills, and are not suitable for production sites.
[0005] Therefore, there is an urgent need for a surface defect detection method for aluminum alloy plates that has a simple process, can be applied to production sites, has high detection accuracy, fast speed and low cost. Summary of the invention
[0006] In view of the shortcomings and deficiencies of the above-mentioned prior art, the present invention provides a method for detecting surface defects of aluminum alloy plates. The present invention creatively adopts a detection method combining degreasing and electrolysis of polishing liquid. Specifically, on the one hand, the present invention adopts a degreasing treatment to remove grease from the surface of the aluminum alloy plate to ensure the cleanliness of the aluminum alloy surface. On the other hand, the electrolytic polishing method is usually used to make the surface of the metal plate flat and smooth (that is, polishing in the conventional sense), but the inventors have gone the other way and creatively used polishing liquid to electrolyze the aluminum alloy plate, so as to effectively remove oxides and hydroxides on the surface of the plate, and at the same time further expand the depth of microcracks, increase the storage capacity of the defective part for the penetrant, and prevent the complete loss of the penetrant caused by cleaning, thereby enhancing the ability of the colored penetrant to identify microcracks on the surface of the plate.
[0007] The specific plan is as follows:
[0008] A method for detecting surface defects of an aluminum alloy plate, the method comprising the following steps:
[0009] S1. Pre-treating the aluminum alloy plate sample to be tested;
[0010] S2, using a degreasing agent to degrease the sample to be tested;
[0011] S3, placing the sample in an acidic polishing solution for electrolytic treatment to enlarge the size of micro defects, connecting the degreased sample as an anode material to the positive electrode of a power supply, and connecting the cathode material to the negative electrode of a power supply;
[0012] S4, washing the electrolyte remaining on the surface of the sample after the electrolysis treatment with water, drying it, and then performing a penetration treatment with a colorant;
[0013] S5. Visually observe the surface of the sample after colorant penetration treatment to determine whether there are defects on the surface of the aluminum alloy plate.
[0014] Furthermore, the surface defects of the aluminum alloy plate include micro defects with a depth of less than 50 μm. Only conventional penetrant flaw detection methods cannot effectively identify micro cracks of this size level.
[0015] Preferably, the pretreatment in step S1 includes: cutting the test sample with a size of 5-10 cm×10-20 cm, grinding the edge with 500-4000 mesh sandpaper, and removing burrs generated by cutting and other treatments.
[0016] Preferably, the degreasing treatment in step S2 is performed at a temperature of 10 to 80° C. and for a time of 0.5 to 30 min.
[0017] Furthermore, the acidic polishing liquid in step S3 is composed of 85% H 3 PO 4 , 30-50% by volume of 98% concentrated H 2 SO 4 The polishing liquid is mixed with a complexing agent with a concentration ratio of 0.2 to 5 g / L, and the pH value of the polishing liquid is adjusted to 2 to 4 with a dilute alkali solution.
[0018] Preferably, the complexing agent is thiourea, tartaric acid or polyethylene glycol, and the dilute alkali solution is dilute NaOH solution.
[0019] Preferably, the cathode material in step S3 is stainless steel or graphite plate.
[0020] Furthermore, in step S3, the distance between the anode material and the cathode material is set to 3-10 cm, and the current density of the electrolysis process is controlled to 5-25 A / dm 2 , the temperature is set at 8-60°C, and the electrolysis time is controlled at 1-30 minutes.
[0021] Preferably, the acidic polishing liquid is composed of 85% H 3 PO 4 , 50% by volume of 98% concentrated H 2 SO 4 It is mixed with a complexing agent at a concentration ratio of 0.5g / L, and the pH value is 2-3.
[0022] Preferably, the distance between the anode material and the cathode material is about 5 cm, and the current density of the electrolysis process is controlled to be about 8 A / dm 2 , the temperature was set at about 40°C and the electrolysis time was controlled to about 3 minutes.
[0023] The beneficial effects of the present invention are:
[0024] ① The present invention uses a degreasing process in combination with an electrolytic polishing process, which can effectively remove grease from the surface of the plate and ensure the cleanliness of the aluminum alloy surface. The electrolytic polishing process can effectively remove oxides and hydroxides from the surface of the plate, and can further expand the depth of the cracks, thereby enhancing the ability of the penetrant flaw detector to identify microcracks on the surface of the plate. In particular, it has a good identification effect on cracks with a depth of less than 50μm.
[0025] ② The polishing liquid used in the present invention has low usage, can be recycled and reused multiple times, has little environmental pollution and low cost.
[0026] ③ The complexing agent and cathode material are easy to obtain and have excellent effects.
[0027] ④ The electrolysis process of the present invention is simple, quick and convenient to operate, the equipment cost is low, and the detection results are intuitive. It has great prospects in the detection and identification of surface defects of aluminum alloy plates. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the detection process of the method of the present invention. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Unless otherwise specified, all terms used in the specification have the meanings commonly understood by those skilled in the art. For the sake of brevity and / or clarity, well-known functions or structures are not described in detail.
[0031] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0032] First, cut a sample from the aluminum alloy plate to be tested. The size of the sample can be controlled to 5-10cm×10-20cm. If necessary, the cut edge of the sample can be polished with 500-4000 mesh sandpaper to remove burrs generated by cutting and other processes. Note that damage to the surface of the sample to be tested should be avoided.
[0033] Then, the obtained sample is degreased with a degreasing agent. The degreasing agent may be, for example, a weak alkaline degreasing agent, an acidic degreasing agent, an organic solvent, or a mixed solution of the above degreasing agents. The temperature of the degreasing treatment may be controlled at 10 to 80°C, and the time may be controlled at 0.5 to 30 minutes. Through the degreasing treatment, impurities such as grease on the surface of the sample may be removed, otherwise these impurities will greatly hinder the penetration of the colorant into the cracks on the surface of the sample in the subsequent colorant penetration treatment.
[0034] Next, an acidic polishing solution for electrolysis is prepared. The polishing solution may contain 85% H 3 PO 4 , 30-50% by volume of 98% concentrated H 2 SO 4 , the concentration ratio of the complexing agent is 0.2-5 g / L. The pH value of the polishing liquid can be adjusted to about 2-4 with a dilute alkali solution such as a dilute NaOH solution. The complexing agent can preferably use thiourea, tartaric acid and polyethylene glycol.
[0035] After the polishing liquid is prepared, the polishing liquid is placed in the electrolytic cell. The power source for electrolysis can be a DC power supply. The degreased sample is connected to the positive pole of the power supply as the anode material, and the cathode material is connected to the negative pole of the power supply. Preferably, the cathode material is stainless steel or a graphite plate. The cathode material is placed parallel to the anode material, and the distance between the two can be set to 3 to 10 cm. During the electrolysis process, the current density can be controlled to 5 to 25 A / dm 2 , the temperature can be set at 8-60°C, and the electrolysis time can be controlled to be 1-30 minutes. The acid polishing liquid electrolysis process can effectively remove oxides and hydroxides on the surface of aluminum alloy plate samples, and can further expand the depth of microcracks on the surface of the sample. Therefore, the penetrant's ability to identify microcracks on the plate surface can be improved in the subsequent colorant penetration treatment.
[0036] If necessary, the aluminum alloy plate sample can be rinsed with deionized water after the electrolytic treatment to remove the electrolyte (i.e., polishing liquid) that may remain on the surface of the sample. The rinsed sample needs to be dried. For example, the drying process can be carried out in a drying oven, the drying temperature can be set to 5 to 100°C, and the time can be controlled to 5 to 120 minutes.
[0037] Then, the sample is subjected to a colorant penetration treatment, also known as a penetrant flaw detection treatment. The standard for the penetration detection method may be JB / T 6062~1992. The colorant (also known as a penetrant or fluorescent agent) may be a commercially available Hongda brand HD~ST type. The colorant will penetrate into cracks that may exist on the surface of the aluminum alloy plate sample. The deeper the crack, the deeper the colorant penetrates, and the less likely it is to be lost during, for example, the later cleaning process. Since the aforementioned electrolysis process increases the size (depth and width) of microcrack-type defects, the storage capacity of the defective part for the colorant is also increased, and the subsequent coloration of the defective part will be more obvious. As a result, tiny cracks on the aluminum alloy surface that cannot be identified by penetrant flaw detection alone can be effectively identified.
[0038] Finally, visually observe the aluminum alloy plate sample after the colorant penetration treatment. The flat part of the sample surface without cracks will be covered by the white developer. If there are cracks on the sample surface, red will appear on the white developer. If no red is observed on the white developer, it can be confirmed that there are no defects on the sample surface.
[0039] It should be noted that the above steps are not all necessary, but one or more of the above steps may be omitted or one or more other steps may be added as appropriate. For example, if the edge of the obtained sample is smooth and flat, there is no need to perform the grinding and deburring step.
[0040] The following will further illustrate the method for detecting surface defects of the aluminum alloy plate according to the present invention in combination with the following embodiments and comparative examples.
[0041] Example 1
[0042] (1) Deburring: Cut aluminum alloy plates with known surface defects and control the size of the plates to 10 cm × 10 cm. Grind the edges of the plates with 800 and 1000 grit sandpaper to remove burrs generated by cutting and other processes.
[0043] (2) Degreasing treatment: using a degreasing agent to degrease the plate treated in step (1), the degreasing treatment temperature is controlled at 40° C., and the time is 10 minutes.
[0044] (3) Prepare the polishing liquid by mixing 50% by volume of 85% H 3 PO 4 , the product ratio is 50% of 98% concentrated H 2 SO 4 The body is mixed with a complexing agent with a concentration ratio of 0.5g / L, and the pH value of the polishing liquid is adjusted to 2.5 with a dilute alkali solution.
[0045] (4) electrolysis, placing the solution prepared in step (3) in an electrolytic cell; using a DC power supply as a power source, connecting the aluminum alloy plate treated in step (2) to the positive electrode of the DC power supply, connecting the cathode material to the negative electrode of the DC power supply, and controlling the cathode plate and the anode material to be placed parallel to each other with a distance of 5 cm between them; controlling the current density of the electrolysis process to be 8 A / dm 2 , temperature is 40℃, and electrolysis time is 3min.
[0046] (5) Rinse the aluminum alloy plate treated in step (4) with deionized water to remove residual electrolyte on the surface.
[0047] (6) Drying: Dry the plate treated in step (5) for 5 min at a temperature of 50°C.
[0048] (7) Penetrant testing: using a colored penetrant testing agent to perform color penetrant testing on the aluminum alloy plate treated in step (6).
[0049] (8) Observation: On the surface of the sample after the colorant penetration treatment, red color was clearly observed on the surface of the white developer.
[0050] Example 2
[0051] (1) Deburring: Cut aluminum alloy plates with known surface defects and control the size of the plates to 10 cm × 10 cm. Grind the edges of the plates with 800 and 1200 grit sandpaper to remove burrs generated by cutting and other processes.
[0052] (2) Degreasing treatment: using a degreasing agent to degrease the plate treated in step (1), the degreasing treatment temperature is controlled at 25° C., and the time is 5 minutes.
[0053] (3) Prepare the polishing liquid by mixing 60% by volume of 85% H 3 PO 4 , the product ratio is 40% of 98% concentrated H 2 SO 4 The body is mixed with a complexing agent with a concentration ratio of 2.5g / L, and the pH value of the polishing liquid is adjusted to 3.5 with a dilute alkali solution.
[0054] (4) electrolysis, placing the solution prepared in step (3) in an electrolytic cell; using a DC power supply as a power source, connecting the aluminum alloy plate treated in step (2) to the positive electrode of the DC power supply, connecting the cathode material to the negative electrode of the DC power supply, and controlling the cathode plate and the anode material to be placed parallel to each other with a distance of 4 cm between them; controlling the current density of the electrolysis process to be 5 A / dm 2 , temperature is 30℃, electrolysis time is 1.5min.
[0055] (5) Rinse the aluminum alloy plate treated in step (4) with deionized water to remove residual electrolyte on the surface.
[0056] (6) Drying: Dry the plate treated in step (5) for 5 minutes at a temperature of 65°C.
[0057] (7) Penetrant testing: using a colored penetrant testing agent to perform color penetrant testing on the aluminum alloy plate treated in step (6).
[0058] (8) Observation: Red penetration of the white developer can be clearly observed on the surface of the treated plate.
[0059] Example 3
[0060] (1) Deburring: Cut aluminum alloy plates with known surface defects and control the size of the plates to 10 cm × 20 cm. Grind the edges of the plates with 500 and 2000 grit sandpaper respectively to remove burrs generated by cutting and other processes.
[0061] (2) Degreasing treatment: using a degreasing agent to degrease the plate treated in step (1), the degreasing treatment temperature is controlled at 10° C., and the time is 30 minutes.
[0062] (3) Prepare the polishing liquid by mixing 85% H 3 PO 4 , the product ratio is 30% of 98% concentrated H 2 SO 4The body is mixed with a complexing agent with a concentration ratio of 0.2g / L, and the pH value of the polishing liquid is adjusted to 2 with a dilute alkali solution.
[0063] (4) electrolysis, placing the solution prepared in step (3) in an electrolytic cell; using a DC power supply as a power source, connecting the aluminum alloy plate treated in step (2) to the positive electrode of the DC power supply, connecting the cathode material to the negative electrode of the DC power supply, and controlling the cathode plate and the anode material to be placed in parallel with each other, with a distance of 3 cm between them; controlling the current density of the electrolysis process to be 15 A / dm 2 , temperature is 10℃, electrolysis time is 30min.
[0064] (5) Rinse the aluminum alloy plate treated in step (4) with deionized water to remove residual electrolyte on the surface.
[0065] (6) Drying: Dry the plate treated in step (5) for 5 minutes at a temperature of 100°C.
[0066] (7) Penetrant testing: using a colored penetrant testing agent to perform color penetrant testing on the aluminum alloy plate treated in step (6).
[0067] (8) Observation: Red penetration of the white developer can be clearly observed on the surface of the treated plate.
[0068] Example 4
[0069] (1) Deburring: Cut aluminum alloy plates with known surface defects and control the size of the plates to 10 cm × 10 cm. Grind the edges of the plates with 1000 and 4000 grit sandpapers to remove burrs generated by cutting and other processes.
[0070] (2) Degreasing treatment: using a degreasing agent to degrease the plate treated in step (1), the degreasing treatment temperature is controlled at 80° C., and the time is 5 minutes.
[0071] (3) Prepare the polishing liquid by mixing 55% by volume of 85% H 3 PO 4 , the product ratio is 45% of 98% concentrated H 2 SO 4 The body is mixed with a complexing agent with a concentration ratio of 5g / L, and the pH value of the polishing liquid is adjusted to 4 with a dilute alkali solution.
[0072] (4) electrolysis, placing the solution prepared in step (3) in an electrolytic cell; using a DC power supply as a power source, connecting the aluminum alloy plate treated in step (2) to the positive electrode of the DC power supply, connecting the cathode material to the negative electrode of the DC power supply, and controlling the cathode plate and the anode material to be placed in parallel with each other, with a distance of 10 cm between them; controlling the current density of the electrolysis process to be 25 A / dm 2, temperature is 60℃, electrolysis time is 1min.
[0073] (5) Rinse the aluminum alloy plate treated in step (4) with deionized water to remove residual electrolyte on the surface.
[0074] (6) Drying: Dry the plate treated in step (5) for 120 min at a temperature of 5°C.
[0075] (7) Penetrant testing: using a colored penetrant testing agent to perform penetrant color development on the aluminum alloy plate treated in step (6).
[0076] (8) Observation: Red penetration of the white developer can be clearly observed on the surface of the treated plate.
[0077] Comparative Example 1
[0078] (1) Deburring: Cut aluminum alloy plates with known surface defects and control the size of the plates to 5 cm × 10 cm. Grind the edges of the plates with 500-4000 grit sandpaper to remove burrs generated by cutting and other processes.
[0079] (2) Degreasing treatment: using a degreasing agent to degrease the plate treated in step (1), the degreasing treatment temperature is controlled at 50° C., and the time is 20 minutes.
[0080] (3) Prepare the polishing solution by mixing 65% by volume of 85% H 3 PO 4 , the product ratio is 35% of 98% concentrated H 2 SO 4 The body is mixed with a complexing agent with a concentration ratio of 2.5g / L, and the pH value of the polishing liquid is adjusted to 3.5 with a dilute alkali solution.
[0081] (4) The degreased sample is chemically treated by placing it in the prepared polishing liquid and treating it at 30°C for 8 minutes.
[0082] (5) Rinse the aluminum alloy plate treated in step (4) with deionized water to remove residual electrolyte on the surface.
[0083] (6) Drying: Dry the plate treated in step (5) for 20 min at a temperature of 50°C.
[0084] (7) Penetrant testing: using a colored penetrant testing agent to perform penetrant color development on the aluminum alloy plate treated in step (6).
[0085] (8) Observation shows that only white developer can be observed on the surface of the sample after the colorant penetration treatment, but no red color is observed. This indicates that if the aluminum alloy plate sample is not electrolytically treated with a polishing liquid as in the present invention, micro defects on the surface of the aluminum alloy plate cannot be effectively identified.
[0086] Comparative Example 2
[0087] (1) Deburring: Cut aluminum alloy plates known to have no surface defects and control the size of the plates to 5 cm × 10 cm. Grind the edges of the plates with 800 and 1200 grit sandpaper respectively to remove burrs generated by cutting and other processes.
[0088] (2) Degreasing treatment: using a degreasing agent to degrease the plate treated in step (1), the degreasing treatment temperature is controlled at 25° C., and the time is 5 minutes.
[0089] (3) Prepare the polishing liquid by mixing 60% by volume of 85% H 3 PO 4 , the product ratio is 40% of 98% concentrated H 2 SO 4 The body is mixed with a complexing agent with a concentration ratio of 2.5g / L, and the pH value of the polishing liquid is adjusted to 3.5 with a dilute alkali solution.
[0090] (4) electrolysis, placing the solution prepared in step (3) in an electrolytic cell; using a DC power supply as a power source, connecting the aluminum alloy plate treated in step (2) to the positive electrode of the DC power supply, connecting the cathode material to the negative electrode of the DC power supply, and controlling the cathode plate and the anode material to be placed parallel to each other with a distance of 4 cm between them; controlling the current density of the electrolysis process to be 5 A / dm 2 , temperature is 30℃, electrolysis time is 1.5min.
[0091] (5) Rinse the aluminum alloy plate treated in step (4) with deionized water to remove residual electrolyte on the surface.
[0092] (6) Drying: Dry the plate treated in step (5) for 10 min at a temperature of 65°C.
[0093] (7) Penetrant testing: using a colored penetrant testing agent to perform color development treatment on the aluminum alloy plate treated in step (6).
[0094] (8) Observation shows that only white developer can be observed on the surface of the sample after the colorant penetration treatment, and no red color is revealed. This indicates that no defects on the surface of the aluminum alloy plate are identified. It can be seen that, except that the sample to be tested is an aluminum alloy plate known to have no surface defects, the other process steps and parameters of Comparative Example 2 are basically the same as those of Example 2. Consistent with the actual situation, Comparative Example 2 identifies that there are no defects on the surface of the aluminum alloy plate. This further illustrates that the detection method of the present invention is effective. By using the specific polishing liquid composition and electrolysis control parameters defined in the present invention, the electrolysis process will not produce new defects that do not exist on the surface of the aluminum alloy plate sample, thereby causing distortion of the detection results.
[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for detecting surface defects of aluminum alloy plates, characterized in that: The detection method comprises the following steps: S1. Pre-treating the aluminum alloy plate sample to be tested; S2, using a degreasing agent to degrease the sample to be tested; S3, placing the sample in an acidic polishing solution for electrolytic treatment to enlarge the size of micro defects and extend the depth of micro cracks on the surface of the sample, connecting the degreased sample as an anode material to the positive electrode of a power supply, and connecting the cathode material to the negative electrode of a power supply; S4, washing the electrolyte remaining on the surface of the sample after the electrolysis treatment with water, drying it, and then performing a penetration treatment with a colorant; S5. Visually observe the surface of the sample after the colorant penetration treatment to determine whether there are defects on the surface of the aluminum alloy plate; The acidic polishing liquid in step S3 is prepared by mixing 85% H3PO4 with a volume ratio of 50-70%, 98% concentrated H2SO4 with a volume ratio of 30-50%, and a complexing agent with a concentration ratio of 0.2-5 g / L, and the pH value of the polishing liquid is adjusted to 2-4 with a dilute alkali solution; The complexing agent is thiourea, tartaric acid or polyethylene glycol, and the dilute alkali solution is dilute NaOH solution; In step S3, the distance between the anode material and the cathode material is set to 3-10 cm, and the current density of the electrolysis process is controlled to 5-25 A / dm 2 , the temperature is set at 8-60°C, and the electrolysis time is controlled at 1-30 minutes.
2. The detection method according to claim 1, characterized in that: The surface defects of the aluminum alloy plate include micro defects with a depth of less than 50 μm.
3. The detection method according to claim 1, characterized in that: The pretreatment in step S1 includes: cutting the test sample with a size of 5-10 cm×10-20 cm, grinding the edge with 500-4000 mesh sandpaper, and removing burrs generated by the cutting process.
4. The detection method according to claim 1, characterized in that: The degreasing treatment in step S2 is performed at a temperature of 10 to 80° C. and for a time of 0.5 to 30 minutes.
5. The detection method according to claim 1, characterized in that: The cathode material in step S3 is stainless steel or graphite plate.
6. The detection method according to claim 1, characterized in that: The acid polishing liquid is prepared by mixing 85% H3PO4 with a volume ratio of 50%, 98% concentrated H2SO4 with a volume ratio of 50% and a complexing agent with a concentration ratio of 0.5g / L, and the pH value is 2-3.
7. The detection method according to claim 1, characterized in that: The distance between the anode material and the cathode material is 5 cm, and the current density of the electrolysis process is controlled to 8 A / dm 2 , the temperature was set at 40°C and the electrolysis time was controlled to 3 min.
Citation Information
Patent Citations
Metal streamline corrosion method
CN104977247A
Acid etching method for displaying macrostructures and flaws of corrosion resistant alloy
CN109765085A
Composition for detecting flaws of surfaces of aluminium and its alloys
SU1532853A1